Nonprofessional Investor Judgments: Linking Dependent Measures to Constructs - Asay, H. Scott; Hales, Jeffrey; Hinds, Cory; Rupar, Kathy (The Accounting Review, 2023)
ABSTRACT There is limited evidence on the construct validity of the dependent measures commonly used in the literature on nonprofessional investor judgments. In this paper, we first survey the literature to understand the types of dependent measures typically used by researchers. We then conduct factor analyses to uncover linkages between dependent measures and the constructs underlying these nonprofessional investor judgments. Our results suggest that, while the wide variety of dependent measures can appear on their face to represent many nuanced economic constructs, these measures capture three distinct factors. These factors relate to nonprofessional investors’ (1) expectations regarding future firm performance and value, (2) holistic perceptions of the firm, and (3) evaluations of the risk associated with investing in the firm. Next, we provide recommendations for selecting, analyzing, and reporting dependent measures in future research. Finally, we provide directions for future research to further our understanding of the judgments made by investors.